The revolution of Muhammad bin Abdullah Al-Massi and its impact on Almohad rule - ورده, زينب (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The Almohad state is considered one of the most important empires that arose in the Islamic Maghreb in the medieval period, after its success in eliminating the Almoravid rule in the year 541 AH/1147 AD, and its success in extending its control over the entirety of North Africa in its various sections (the lower, middle, and far Morocco), and then extending it to... The country of Andalusia, and thus the Almohads established a powerful and feared state that was able to maintain its political and geographical unity for a long period of time, as a result of the existence of a centralized and strict political and administrative system. Despite the political stability in the Almohad state, the large geographical expansion, the state’s preoccupation with external wars, and consequently the caliphs’ neglect of internal affairs, led to the emergence of a number of internal disturbances and rebellions, in the various stages of the state, which prompted the Almohad authorities to prepare armies to eliminate those Revolutions, and stopping their danger. Perhaps one of the most important of those revolutions that took place was the revolution of Muhammad bin Abdullah Al-Massi. What are its causes, events, and results?